URBAN FARMING AND FOOD SECURITY ETHICS: A STUDY FROM THE PERSPECTIVE OF PROPHETIC HADITH - Rahman; Mashuri; Suardi; Muhammad Abdi alMaktsur; Wasalmi (Qolamuna : Jurnal Studi Islam, 2026)
Food security has emerged as a critical global issue, particularly in urban areas experiencing rapid population growth, land scarcity, and ecological challenges. Urban farming is increasingly recognized as an innovative and sustainable solution to strengthen food security in cities. However, discussions on urban farming often focus on technical and economic dimensions, while ethical and spiritual perspectives—especially from Islamic teachings—remain underexplored. This study aims to examine food security ethics and urban farming practices from the perspective of the Hadith of Prophet Muhammad (peace be upon him). Using a qualitative library-based research method, this study employs a thematic (maudhu‘i) hadith analysis to identify prophetic traditions related to food production, environmental stewardship, self-sufficiency, moderation, and social responsibility. The findings reveal that the Hadith strongly encourages productive land use, even in limited spaces, emphasizes the moral obligation to ensure food availability, and promotes sustainable interaction with nature. Principles such as avoiding waste (israf), maintaining balance (mizan), fostering communal welfare, and ensuring justice in food distribution are deeply embedded in prophetic teachings. Urban farming, when viewed through this ethical framework, is not merely an agricultural practice but a form of worship (‘ibadah) and social responsibility that aligns with Islamic values. This study contributes to interdisciplinary discourse by integrating Islamic ethical perspectives with contemporary urban food systems and offers a normative foundation for developing faith-based food security policies. The findings are expected to enrich Islamic studies, environmental ethics, and sustainable urban development, particularly in Muslim-majority urban contexts. Keywords : Islamic Environmental Ethics; Food Security; Urban Farming; Hadith Studies